2014
DOI: 10.1128/mmbr.00015-14
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Peptidyl-Prolyl cis / trans Isomerases (PPIases): Virulence Factors and Potential Alternative Drug Targets

Abstract: SUMMARY Initially discovered in the context of immunomodulation, peptidyl-prolyl cis/trans isomerases (PPIases) were soon identified as enzymes catalyzing the rate-limiting protein folding step at peptidyl bonds preceding proline residues. Intense searches revealed that PPIases are a superfamily of proteins consisting of three structurally distinguishable families with representatives in every described species of prokaryote and eukaryote and, recently, even in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
155
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(156 citation statements)
references
References 293 publications
(402 reference statements)
1
155
0
Order By: Relevance
“…Traditional antibiotic development approaches that target a limited number of bacterial components are increasingly ineffective, and therefore, novel bacterial targets must be investigated. PPIase enzymes represent one such promising novel target (2). The work presented here demonstrates that two functionally distinct PPIases are important for virulence factor production in S. aureus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional antibiotic development approaches that target a limited number of bacterial components are increasingly ineffective, and therefore, novel bacterial targets must be investigated. PPIase enzymes represent one such promising novel target (2). The work presented here demonstrates that two functionally distinct PPIases are important for virulence factor production in S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, for all other naturally occurring amino acids, steric hindrance between side chains precludes the cis form and overwhelmingly favors the trans form (2). The presence of both the cis and trans forms of proline peptide bonds has important consequences for protein tertiary structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…I presume that the majority of DFIs are functional PPIases and may also have the expected chaperone activity. As a corollary, they may be explored as therapeutic targets (Schiene-Fischer 2015;Ünal and Steinert 2014), perhaps through the designing of selective bispecific drugs (Dunyak et al 2015;Yang et al 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical analyzes revealed that the collagen-derived peptide P290 binds to a specific hydrophobic cavity of Mip, and based on NMR data and docking studies a model for the mode of interaction of P290 and Mip was developed. Moreover, guinea pig infections revealed that Mip contributes to alveolar septum transmigration of L. pneumophila and subsequently to the bacterial spread to the spleen (Cianciotto et al, 1995;Uenal et al, 2011;Ünala and Steinert, 2014;Wagner et al, 2007).…”
Section: Introductionmentioning
confidence: 98%